Impacts of the New York State COVID‐19 disaster emergency orders on prescription dispensing for opioids and medication for opioid use disorder. (12th December 2022) - Suri, Abhinav; Feaster, Daniel J.; Balise, Raymond R.; Quinn, James; Nunes, Edward V.; Gilbert, Louisa; El‐Bassel, Nabila; Rundle, Andrew G.
Abstract: Aims: The aim of this study is to examine whether the March 2020 New York State (NYS) SARS‐CoV‐2 emergency orders were associated with an initial surge in opioid dispensing and a longer‐term reduction in access to medications for opioid use disorder (MOUD). Design: Time‐series analyses of the dispensing of non‐MOUD opioid and MOUD prescriptions using IQVIA's longitudinal prescription claims database ( n  = 16 087 429) in NYS by week, from 1 January 2018 to 31 July 2020. IQVIA is a multi‐national company that provides biopharmaceutical development and commercial outsourcing services. Setting and Participants: NYS Zone Improvement Plan (ZIP) codes ( n  = 1218) in which prescriptions were dispensed. Measurement: For each ZIP code, for each week, the following dispensing measures were calculated: total weekly morphine milligram equivalents/day (MME/day), total weekly MME/day dispensed via prescriptions for ≤ 7 days and the count of MOUD prescriptions dispensed. Differences in dispensing metrics, comparing each week in 2020 with corresponding weeks in 2019, were calculated for each ZIP code. Results: During the study period, weekly MME/day per ZIP code of dispensed non‐MOUD opioids steadily declined. Compared with the difference in dispensing between 2019 and 2020 during the first week in 2020, there was a significantly larger drop in dispensed weekly total MME/day beginning 21 March 2020, and lasting until the week of 17 April ( P  < 0.05 for each week). Mean weekly total MME/day dispensed from 21 March to 17 April 2020 was 17.07% lower [95% confidence interval (CI) = 13.97%, 20.17%] than in the 4 weeks before 21 March almost entirely due to a drop in MME/day dispensed for prescriptions of ≤ 7 days. There was not a discernable drop in MOUD dispensing associated with the period of the emergency orders. Conclusions: New York State emergency orders in March 2020 to reduce SARS‐CoV‐2 transmission and preserve hospital capacity appeared to be associated with a decline in dispensing of opioids not used as MOUD. Access to MOUD appeared to be unaffected by the orders, probably because of policy initiatives by the Substance Abuse and Mental Health Services Administration.